2016
DOI: 10.1089/sur.2015.076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LRINEC Scale Feasibility for Predicting Outcomes of Fournier Gangrene

Abstract: The LRINEC score could be used for prediction of disease severity and outcomes. A threshold of 9 could be a high-value predictor of death during the initial evaluation of patients with FG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
0
28
1
2
Order By: Relevance
“…Some authors propose the use of prognostic factor outcome predictors: Laor et al 22 created the Fournier Gangrene Severity Index (FGSI) that gathers clinical (fever, respiratory rate, heart rate) and laboratory data (serum sodium, potassium, bicarbonate, creatinine, haematocrit and white blood cell count) allowing to predict patients' prognosis and mortality: when the score > 9, the mortality can reach up to 75%, and if < 9 survival can be expected in 78% of the patients, but many authors like Tuncel et al 23 argue that the index cannot be relied on to predict mortality alone; Friederichs et al 24 state that procalcitonin (PCT) ratio levels 1 or 2 days after surgical debridement may be a valuable indicator of infection source elimination, indicating that when PCT values rises, wider margin debridement is required. Kincius M et al 25 evaluated the feasibility of predicting the outcome using the LRINEC (Laboratory Risk Indicator for Necrotizing Fasciitis) score using laboratory data (C-reactive protein, sodium, white blood cell count, hemoglobin, serum sodium, creatinine and glucose); they concluded that a score higher than 9 can be used as a high-value threshold predictor of death during the first evaluation of patients with FG.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors propose the use of prognostic factor outcome predictors: Laor et al 22 created the Fournier Gangrene Severity Index (FGSI) that gathers clinical (fever, respiratory rate, heart rate) and laboratory data (serum sodium, potassium, bicarbonate, creatinine, haematocrit and white blood cell count) allowing to predict patients' prognosis and mortality: when the score > 9, the mortality can reach up to 75%, and if < 9 survival can be expected in 78% of the patients, but many authors like Tuncel et al 23 argue that the index cannot be relied on to predict mortality alone; Friederichs et al 24 state that procalcitonin (PCT) ratio levels 1 or 2 days after surgical debridement may be a valuable indicator of infection source elimination, indicating that when PCT values rises, wider margin debridement is required. Kincius M et al 25 evaluated the feasibility of predicting the outcome using the LRINEC (Laboratory Risk Indicator for Necrotizing Fasciitis) score using laboratory data (C-reactive protein, sodium, white blood cell count, hemoglobin, serum sodium, creatinine and glucose); they concluded that a score higher than 9 can be used as a high-value threshold predictor of death during the first evaluation of patients with FG.…”
Section: Discussionmentioning
confidence: 99%
“…In the original publication, a score of ≥6 yielded a positive predictive value of 92% and negative predictive value of 96%, displaying promise for predicting severity of skin and soft tissue infection among patients presenting to emergency care. Although retrospective validation of this scoring system has been attempted in small case-series 24,25 , a recent multicenter prospective evaluation of the LRINEC score has lessened the excitement around this predictive tool; a cut-off of ≥ or <6 in NSTI patients failed to discriminate between those with and without high cytokine levels, septic shock and death 26 . Furthermore, the LRINEC score can be artificially elevated in other musculoskeletal infections.…”
Section: Diagnosismentioning
confidence: 99%
“…also a good predictor of the severity of the disease [18]. This score is calculated from 6 biological parameters: creatinine, blood glucose, CRP, leukocyte count, hemoglobin, and natremia.…”
Section: Sift Deskmentioning
confidence: 99%
“…Evaluation of the severity of the pathology and the risk of death may be possible using this prognostic score [18]. A score ≥ 9 is associated with a Probability of 93.7% of deaths.…”
Section: Sift Deskmentioning
confidence: 99%